Critical Theory and Feminism Today: An Interview with Karin Stögner - Stögner, Karin; Marino, Stefano; Zampaglione, Ines (Scenari, 2023)
In this contribution we present to the readers of “Scenari” a conversation on critical theory and feminism with the German sociologist Karin Stögner. The text includes four questions written together by Stefano Marino and Ines Zampaglione, and four long, complex and detailed answers to those questions written by Karin Stögner. The questions and answers included in this interview are partly based on the structure and contents of the book Kritische Theorie und Feminismus, co-edited by Karin Stögner with Alexandra Colligs, and published by Suhrkamp press in 2022.